2002
DOI: 10.1111/1468-2311.00238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Probation Based Offender Programmes for Domestic Violence Perpetrators: A Pro‐Feminist Approach

Abstract: Developments in our understanding of domestic violence and its criminalisation have led some probation areas in the UK to adopt pro-feminist offender groupwork programmes as a means of rehabilitating these offenders. The renaissance of the rehabilitative ideal within probation areas has been followed by the need to prove its effectiveness. This article discusses the justifications of providing rehabilitation for this category of offender, outlines the pro-feminist approach and provides a guide to conducting we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…As a result, the provision of community‐based rehabilitation programmes has increased; regional probation areas offered 20 such programmes in 2000 (Humphreys et al , 2000). However, with only three published evaluations from the UK, the effectiveness of these programmes remains unclear (Bowen, Brown, & Gilchrist, 2002). Moreover, the characteristics of those offenders who are most likely to reoffend after attending a rehabilitation programme have never been examined within a British sample.…”
mentioning
confidence: 99%
“…As a result, the provision of community‐based rehabilitation programmes has increased; regional probation areas offered 20 such programmes in 2000 (Humphreys et al , 2000). However, with only three published evaluations from the UK, the effectiveness of these programmes remains unclear (Bowen, Brown, & Gilchrist, 2002). Moreover, the characteristics of those offenders who are most likely to reoffend after attending a rehabilitation programme have never been examined within a British sample.…”
mentioning
confidence: 99%
“…Nor does it discount the benefits of an increased diversity of interventions (see, for example, Women's Services Network 2000; Sharon McCallum and Associates 2002). It is also acknowledged that pro-feminist rehabilitation models are being used to some effect in treating offenders (Bowen et al 2002). However, the renewed individualisation of the problem and the recasting of it as an issue of parenting and partner relationships (Department of Family and Community Services 1999b) is further evidence of the state's rejection of feminist theoretical analyses, and the weakening of women's services through defunding, amalgamation and mainstreaming (Weeks 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Muller (1997) and Bowen et al (2002) have identified several methodological issues concerned with evaluating the effectiveness of programs for domestic violence perpetrators. These issues include: (i) the definition and measurement of successful outcomes (given that male offenders underreport violence, violence may shift from being physical to emotional and corroborating reports from the partner may not be obtainable); (ii) the research design (the lack of a comparison group and the fact that those who complete treatment programs are less prone to re-assault than those who drop out); (iii) sample selection, attrition and the use of validated assessment tools; and (iv) the feasibility of long-term follow up.…”
Section: Methodological and Ethical Issues In Measuring Outcomesmentioning
confidence: 99%
“…The rehabilitative ideal still needs to prove effectiveness in changing abusive behaviour (Bowen, Brown and Gilchrist, 2002). The above studies demonstrate that the evidence of the effectiveness of domestic violence programmes, to the point of declaring best practice, is far from conclusive.…”
Section: Perpetrator Rehabilitation: Efficacy Is Minimalmentioning
confidence: 99%